Forecast for the zone of viticulture in European Russia under climate change - L. Yu. Novikova; P. V. Ozerski (Вавиловский журнал генетики и селекции)
Climate warming has turned out to be a significant factor in viticulture and winemaking in all grape-growing areas of the world. Many countries consider the advance of viticulture to the north and to mountainous areas as a possible way to adapt to warming. The factors limiting the zone of viticulture in Russia have been identified by Soviet scientist F.F. Davitaya in 1948, and they are still relevant. They are the sum of active temperatures above 10 °C (ΣT10 > 2500 °C), mean of absolute minimum temperatures (Tmin > –35 °C), length of the frost-free period (Lff < 150 days), and hydrothermal coefficient (0.5 < HTC < 2.5). The values of these limiting factors in the present-day zone of commercial viticulture (ZCV) correspond to the ranges defined by F.F. Davitaya, with the exception of Tmin, which in the modern ZCV in European Russia is above –26 °C everywhere. The objective of this work was to assess the possibility of moving the boundaries of the ZCV to the north under the existing and predicted climate conditions in European Russia. The 1980–2019 daily data from 150 weather stations of the Federal Service for Hydrometeorology and Environmental Monitoring were used to calculate mean long-term values, trends and forecasts for 2050 for the ZCV limiting factors and locate the points lying in the range acceptable for viticulture. The QGIS program was applied to plot the points on the European Russia map and mark the terminal latitude. Versions with Tmin > –26 °C and Tmin > –35 °C were considered. On average for European Russia, in 1980–2019, there was an increase in ΣT10, Tmin, and Lff and a decrease in HTC. However, in the same period, Tmin showed a tendency toward decreasing at a number of points at latitudes lower than 55° N. The increase in heat supply during the growing season in European Russia implies a possibility of expanding the ZCV northward, beyond the present-day terminal latitude of 46.6° N, to 51.8° N under the existing conditions, and up to 60.7° N by 2050. In addition, even under the current conditions viticulture is possible in the area of Kaliningrad (54° N, 20° E). Using extra protective measures in winters not colder than –35 °C would make it possible to grow grapes at up to 53.3° N under the current conditions and at up to 60.7° N under the prognosticated ones. At the same time, a possible decrease in the minimum winter temperature at the south of European Russia will require additional protective measures in winter, while an increase in the aridity of the climate on the northwest coast of the Caspian Sea will reduce the area under non-irrigated vineyards.